Reliability of the Wingate anaerobic test in cyclists - Bibiano Madrid; Emerson Pardono; Darlan Lopes de Farias; Ricardo Yukio Asano; Roberto Jerônimo dos Santos Silva; Herbert Gustavo Simões (Desafio Singular, 2013)
The aim of this study was to verify the reliability of selected variables during Wingate anaerobic test, physiologic markers and perceptual associated in trained cyclists. Fifteen male cyclists performed three tests, with workload of 0.087 times the body mass. Measures of peak power, average power, minimum power, fatigue index, heart rate, perceived effort and lactate concentration were collected. It was verified data normality, applied ANOVA One Way repeated with Tukey as post-hoc test, intraclass coefficient correlation and Bland Altman test. Results showed no significant different for the peak power, fatigue index, lactate concentration, heart rate and perceived effort between tests. Of these, peak power, heart rate and perceived effort high and significant intraclass correlation scores were found (.797−.975). Also, peak power showed good agreement between tests. In conclusion, the Wingate anaerobic test showed high reliability for peak power, heart rate and perceived effort in recreational cyclists.